Comparison of Weed Floristic Composition in Fruit Gardens in Khorramabad - Sk Mousavi; N. Soori; E Zaidali; N. Azadbakht; M. Ghiasvand (پژوهشهای زراعی ایران, 2011)
Abstract Weed floristic Characteristic of apple, walnut, grape, apricot, nectarine, peach and plum gardens was surveyed in Khorramabad with selection of many garden by randomized sampling method in different regions in 2008. From 86 weed species in fruit garden, most Frequency (86.9 percentage) belonged to perennial weed of field bindweed. Percentage of frequency for field bind weed species was higher than other species. In addition of field bind three other species had 50. Abundance of foxtail, crabgrass, and Johnson grass were 56, 52, 4 and 50% respectively. In this case, four species, 4.7% of population, had 50% abundance or more. Three species of predominant weeds were perennial. Prickly lettuce and common- lambrsquarter with 36.7 and 33.3% abundance compared to other species had relative preference. Among weed species with more than 10% abundance, poaceae family was predominated. Higher level of density (15.9 plants m2) belonged to crabgrass (a perennial weed). In addition to crab grass, also three species in comparison with others had higher level of density. Average pecies density in foxtail, Johnson grass and field bind weed, were 12.3, 8.1 and 7.8 shrub in m2, respectively. Within these four species with a higher level of density, just one species was broad leaf and the other three were grasses. Between six studied fruit gardens, higher level of weed density (137.5 plants m2) belonged to plum garden. Average of weed density in plum garden obviously was more than other gardens. Average weed density in walnut, apricot, apple and grape gardens was 86.4, 84, 76.3 and 75.7 shrub in m2, respectively. High population of weed in plum garden in comparison to other gardens, was due to stability of environment. Overall, 22 grass species was observed in gardens. The highest ratio of perennial species to total population, belonged to plum garden. This ratio in plum garden, was obviously more than other gardens. Grass species of weeds belonged to three families: poaceae, cyperaceae and liliaceae. Within mono cotyledons the highest number of species belonged to poaceae family. Number of species in poaceae and liliaceae families was 18, 2 and 1, respectively. Fabaceae family with 8 species, Brassicaceae and Apiaceae with 4 species and Amaranthaceae, Lamiaceae, Malvaceae and Polygonaceae with 3 species were other abundant families.